Thinking Mathematically (6th Edition)

Published by Pearson
ISBN 10: 0321867327
ISBN 13: 978-0-32186-732-2

Chapter 3 - Logic - 3.6 Negations of Conditional Statements and De Morgan's Law - Exercise Set 3.6 - Page 178: 9


~q ∧ r

Work Step by Step

~q → ~r As we know, the negation of p → q is p ∧ ∼q. Therefore, the negation of the statement is: ~q ∧ ∼(~r). We can also write this as ~q ∧ r because ~(~r) is the same as r.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.